Case Study I: Development of Laminated Wood Products from Eucalyptus Nitens in the Chilean Context - Vasco-Calle, D (Elsevier, 2024)
This chapter describes the manufacturing of thermally modified Eucalyptus nitens GLULAM products from dry-sawn timber. The wood was classified according to its cut direction and separated into loads to undergo two treatment processes: Thermo-Modified Wood at 190°C (TMW 190) and 210°C (TMW210). The prototype products are made of E. nitens plywood glued with polyvinyl acetate: Type 1 beam (VT 1) made of three TMW190 tapes; (2) Type 2 beams (VT2) made of 10 TMW190 tapes, coverings made of two TMW210; and (3) floors made of two tapes, one TMW190 and one TMW210. The products were evaluated through standard tests, delamination tests for the beams, and dimensional stability tests for the floors and coatings. The results show that heat-treated E. nitens wood is suitable for manufacturing engineering products. The delamination test showed promising results. In addition, the floors and coatings proved to have good dimensional stability. © 2024 Elsevier Ltd. All rights reserved.